KONFORMITAS GENDER: KAUM GAY DI RUANG PUBLIK SYARIAH - Sri Widari (Jurnal Anifa: Studi Gender dan Anak, 2021)
Culturally the gay phenomenon has existed in the historical record of culture in Indonesia. The spread of gays in the country will continue to grow, not even closing the possibility of venturing into sharia circles, including Aceh. The existence of gay people in Langsa city caused a variety of strong reactions in the community. The phenomena ultimately force gays to camouflage in people's lives with conformity that is played slickly and massively. This research is intended to obtain answers about gay conformity in interacting in the sharia earth of Langsa City. Using qualitative descriptive measures, it was found that most gays in Langsa City always strive to demonstrate gender conformity to hide their true identity from the wider community. This is done to realize a sense of security and as a existed self-protection against discriminate people of Langsa City who uphold the values of Islamic sharia. So that with the gender conformity carried out by gays in Langsa city will create a calm because gays will feel protected from all prejudices and suspicions of the community.